Efektivitas Model Problem-Based Learning (PBL) Terhadap Keterampilan Pemecahan Masalah di Sekolah Dasar - Nurjanah, Erni; Darmawan , Nurani Hadnistia; El Khuluqo, Fadilah (Didactical Mathematics, 2024)
The aim of this research is to analyze mathematical problem solving abilities through the Problem-Based Learning (PBL) model in class IV of SDN 04 Cibadak Sukabumi for the 2022/2023 academic year. This research uses a type of quantitative research with quasi-experimental design (QuasiExperimental Design), the research design uses Non-equivalent Control Group Design. The sample in this study was 39 grade IV students, then divided into 2 groups. The first group (experimental) consisted of 19 students and the second group (control) consisted of 20 students. The instrument applied in this research is a description test of problem solving abilities. The data analysis technique uses descriptive statistics and inferential statistics, namely the independent samples T-Test. The results of this research reveal that the mathematical problem solving abilities of students in the experimental class are higher than those of control class students. This can be seen from the average score of the experimental class students' mathematical problem solving ability test results, namely 76.87, while the average score for the control class is 71.85. Likewise, the results of the calculation of the independent samples T-Test on the pretest and posttest results for both groups stated that Ho was rejected and Ha was accepted because sig. 0.004 < 0.05,. So the conclusion from the results of this research is that mathematics learning on the subject of KPK and FPB using the Problem-Based Learning (PBL) model has an effect on students' mathematical problem solving abilities